Obstructive Mucus Plug in the Prone Position - Darren Raphael; Sharon Lin; Cecilia Canales; Keith Beaulieu; Cameron Ricks (Association of American Medical Colleges, 2015)
Abstract Introduction This resource contains a medical simulation in which a 42-year-old male smoker undergoing a T7-T8 laminectomy and fusion in the prone position suddenly develops complete airway obstruction shortly after dissection has begun. This case provides an opportunity to discuss the risks associated with prone positioning, management of a patient who is a heavy smoker, as well as crisis resource management (CRM) in the setting of acute airway obstruction. It also highlights a commonly encountered phenomenon occurring in a field avoidance scenario and requires prompt diagnosis and timely management of loss of end tidal carbon dioxide (ETCO2) and ventilation. Methods The case requires the learner to troubleshoot the airway obstruction while in the prone position and make a determination that the patient needs to be positioned supine in order to properly assess the airway. Results This scenario has been delivered 12 times to anesthesia residents with good results, although not all the residents determined the root cause of the airway issue. This scenario has also been used by fully trained anesthesiologists participating in Maintenance in Certification of Anesthesia (MOCA) courses three times to date. In 92% of the cases, the residents initiated a termination of surgery and re-positioned the patient (supine) to assess/optimize an airway. In 100% of the cases performed during MOCA course the patient was suctioned and repositioned supine. Discussion In addition to giving learners an opportunity to troubleshoot an airway obstruction while in the prone position, this case presents excellent examples to highlight the core principles of CRM: Call for help early, anticipate and plan, know the environment, use all information, allocate attention wisely, mobilize resources, use cognitive aids, communicate effectively, distribute the workload, establish role clarity, and designate leadership. CRM will be discussed using reflective debriefing at the conclusion of the case. Overall, a total of 15 providers have had this case presentation and 40 providers have surveyed the case and participated in the debriefing sessions following the scenarios.